2007
DOI: 10.1055/s-2006-958467
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Characterization for Male Fertility and Prostate Cancer: Kallikrein-Related Serine Proteases and Whole Proteome Approaches

Abstract: The kallikrein-related ( KLK) protease gene family encodes a subgroup of 15 serine proteases that includes prostate-specific antigen (PSA) or KLK3, the well-known biomarker for prostate cancer. PSA is also a major component of seminal fluid. To date, 10 other KLK serine proteases have been documented as present in seminal fluid (KLKs 1, 2, 4, 5, 6, 8, 10, 11, 13, and 14) and, like PSA, have the potential to contribute to male fertility, either directly or indirectly, by means of their proteolytic activity on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 144 publications
(219 reference statements)
0
41
0
Order By: Relevance
“…KLK3 expression is restricted to the prostate and hence it is also known as the prostate-specific antigen (PSA). In normal prostate physiology, KLK3 cleaves fibronectin and the seminal-gel-forming proteins semenogelin 1 and semenogelin 2, leading to semen liquefaction and enhanced sperm motility [109][110][111][112][113] (FIG. 3a).…”
Section: Kallikrein Proteases In Physiology and Diseasementioning
confidence: 99%
“…KLK3 expression is restricted to the prostate and hence it is also known as the prostate-specific antigen (PSA). In normal prostate physiology, KLK3 cleaves fibronectin and the seminal-gel-forming proteins semenogelin 1 and semenogelin 2, leading to semen liquefaction and enhanced sperm motility [109][110][111][112][113] (FIG. 3a).…”
Section: Kallikrein Proteases In Physiology and Diseasementioning
confidence: 99%
“…They have also shown that this observation is similar to that of breast cancer, where the loss of ZAG production was associated with the lack of tumor differentiation. It is interesting to note that the expression of ZAG in prostate cancer is similar to that of other relevant prostatic proteins (57), such as prostate-specific antigen and prostatic acid phosphatase, which are significantly decreased in prostatic tumors (63)(64)(65). Moreover, immunohistochemical studies assured the partial loss of ZAG expression in prostatic tissue after malignant transformation (47).…”
Section: Zag and Cancermentioning
confidence: 99%
“…Prostatic fluid accounts for 20-30% of seminal volume and contains high concentrations of citric acid, zinc and specific enzymes. Two major ones are prostate acid phosphatase (PAP) and prostate-specific antigen (PSA) (Veveris-Lowe et al 2007, Graddis et al 2011. The major function of the protease PSA is to liquefy the semen coagulum, although PSA has become better known as a biomarker for prostate cancer (Tosoian & Loeb 2010).…”
Section: Evs In the Male Reproductive Tractmentioning
confidence: 99%